AB0740 Secukinumab in psoriatic arthritis: high disease burden observed in the corrona psoriasis registry. (15th June 2017) - Gottlieb, AB; Strand, V; Karki, C; Mason, M; Greenberg, J; Jugl, S; Gandhi, KK; Mease, PJ
Abstract : Background: Secukinumab (SEC), a fully human anti–IL-17A monoclonal antibody, has significant efficacy in the treatment of moderate-to-severe psoriasis (Ps) and psoriatic arthritis (PsA), with a favourable safety profile. The Corrona Psoriasis Registry is an independent observational registry of Ps patients (pts) receiving FDA-approved systemic treatments (TNFis, anti–IL-17s and IL-12/23 and non-biologics) in the United States. Objectives: To assess demographics, clinical features and pt reported outcomes (PROs) of Ps pts with concomitant PsA receiving systemic treatments at registry enrolment. Methods: Adult Ps pts who initiated a systemic therapy at enrolment or in the previous 12 months, and concomitant PsA reported by a dermatologist, were included. Demographics (e.g. age, gender, BMI), disease activity (body surface area, investigator global assessment, psoriasis area severity index) and PROs (pain, fatigue, itch, EQ-VAS 0–100, work productivity and activity impairment and dermatology life quality index) were evaluated at enrolment and stratified by therapy: SEC, etanercept (ETN), adalimumab (ADA), ustekinumab (UST), and non-biologics (Non-B). Results: As of October-2016, 2073 Ps pts were enrolled in the registry; 823 (39.7%) had a PsA diagnosis (mean disease duration 7.6 years) of which 37% were biologic naïve. Of the 823 pts with PsA, 25.4% received SEC, 6.2% ETN, 21.5% ADA, 17.6% UST, and 24.8% Non-B. Pts on SEC had a mean age 53.2 years, mean BMI 32.4; 45% were female; all comparable across the treatment groups. PsA pts treated with SEC had higher Ps disease activity than other treated groups (Table). A higher proportion of SEC treated PsA pts had diabetes and cardiovascular disease (25% and 19% respectively). Mean pain scores were higher in the SEC group; however other PROs assessed at enrolment were similar across treatment groups (Table). Conclusions: These data show that Ps pts with concomitant PsA who initiated SEC in the Corrona Psoriasis Registry had higher disease activity, more comorbidities and suffered from more severe pain at enrolment. These differences need to be factored in for future analyses between treatment groups as data mature in this registry. Disclosure of Interest: A. Gottlieb Grant/research support from: (Paid to Tufts Medical Center until 5/11/16, thereafter: None): Centocor (Janssen) Inc., Amgen, Abbott (AbbVie), Novartis, Celgene, Pfizer, Lilly, Levia, Merck, Xenoport, Dermira, Baxalta, Consultant for: Amgen Inc., Astellas, Akros, Centocor (Janssen) Inc., Celgene Corp., Bristol Myers Squibb Co., Beiersdorf Inc., Abbott Labs. (AbbVie), TEVA, Actelion, UCB, Novo Nordisk, Novartis, Dermipsor Ltd., Incyte, Pfizer, Canfite, Lilly, Coronado, Vertex, Karyopharm, CSL Behring Biotherapies for Life, Glaxo SmithKline, Xenoport, Catabasis, Meiji Seika Pharma Co. Ltd, Takeda, Mitsubishi, Tanabe Pharma Development America Inc., Genentech, Baxalta, Kineta One, KPI Therapeutics, Crescendo Bioscience, Aclaris, Amicus and Reddy Labs, V. Strand Consultant for: AbbVie, Amgen, BMS, Celgene, Celltrion, Corrona, Crescendo, Genentech/Roche, GSK, Janssen, Lilly, Merck, Novartis, Pfizer, Regeneron, Samsung, Sanofi and UCB, C. Karki Employee of: Corrona, LLC., M. Mason Employee of: Corrona, LLC., J. Greenberg Shareholder of: Corrona, LLC., Consultant for: AstraZeneca, Celgene, Genentech, Janssen, Novartis and Pfizer, Employee of: Corrona, LLC., S. Jugl Shareholder of: Novartis, Employee of: Novartis, K. Gandhi Shareholder of: Novartis, Employee of: Novartis, P. Mease Grant/research support from: AbbVie, Amgen, BMS, Celgene, Crescendo Bioscience, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, and UCB, Consultant for: Abbvie, Amgen, BMS, Celgene, Crescendo Bioscience, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, and UCB, Speakers bureau: AbbVie, Amgen, BMS, Celgene, Crescendo Bioscience, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer and UCB